THE ASSOCIATION BETWEEN SALAT AND THE PREVENTION OF SPINIAL PAIN: A LITERATURE STUDY - Triana Srisantyorini; Ernyasih Ernyasih; Muhammad Farid Hamzens; Dihartawan Dihartawan; Irna Hasanah (Indonesian Journal of Islam and Public Health, 2021)
Salat is a compulsory worship performed by Muslims 5 times a day and can be supplemented with sunnah worship. Allah requires Muslims to comply with the Qur'an and the Hadith of the Prophet Muhammad. In Salat, there are bowing and prostration movements that cause the spinal muscles to become stretched. This helps the muscles become more elastic and prevents pain in the spine. This article using the literature review by examining 5 journals regarding the association between Salat and the prevention of spinial pain. Journals are downloaded or obtained through the journal portals of universities in Indonesia published in the last 5 years. The results of research from 5 journals that have been reviewed, it can be concluded that if Salat movements such as bowing and prostration are carried out properly or seriously and not in a hurry, then this movement can help restore elasticity of the muscles of the spine and maintain flexibility, so that it can prevent pain in the spine and can be a natural therapy if there is already pain in the spine.